The haunting of Sunshine girl - McKenzie, Paige (McKenzie, Paige. Haunting of Sunshine girl, 2016)
Sixteen-year-old Sunshine Griffith and her mother Kat move from Austin, Texas to Ridgemont, Washington into a house where Sunshine is followed by an icy breeze, a phantom wind slams her bedroom shut, and on her first night she hears laughter that turns into sobs. With her mother in danger, Sunshine must accept what she is to save her.